Language politeness in students’ text messages sent to the lecturers through WhatsApp application: A sociopragmatic study - Miftahush Shalihah; Muhammad Nurdin Zuhdi (Universitas Merdeka Malang, 2020)
Students and lecturers often communicate, both in formal and semi-formal situations. Good communication between students and lecturers remains within the limits of politeness even though it is not in a formal situation. The existence of social media certainly facilitates communication between students and lecturers. This research aims to describe and analyze the politeness of language in short messages from students to lecturers through the WhatsApp application at Universitas 'Aisyiyah Yogyakarta (UNISA). This research employed a qualitative research. The data from this study were 105 conversations between lecturers and students through the WhatsApp messaging application. The analysis in this research was carried out to determine 1) obedience and violation to the tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim and sympathy maxim, 2) forms of language politeness, that are positive face and negative face, and 3) function of language politeness that are representative, directives, expressive, commisive and declaratives. The results showed that most of students used polite language in their text messages and used formal language which contained complete politeness expressions such as greetings, self-introductions, apologies at the beginning and/or at the end of text messages, intention in sending messages, thank you –note and closing. Most of the text employs positive face. Students’ text messages mostly function as representative and directives. DOI: 10.26905/enjourme.v4i2.4926